Investors' attention and the paradox of technologically related diversification: Evidence of stock market mispricing - Morandi Stagni, Raffaele; Santaló, Juan (Strategic Management Journal, 2025)
Abstract Research Summary We show that multi‐business firms pursuing technologically related diversification often face a paradox. While such strategies can yield superior financial performance through technological synergies, investors with limited attention tend to undervalue them due to their complexity. Using asset pricing methods, we find that these firms consistently outperform market expectations. The degree of mispricing depends on investor attention and the availability of information needed to assess the strategy's value. Our findings highlight how informational frictions can distort market valuations of complex corporate strategies. Managerial Summary Firms diversifying across technologically related businesses may unlock significant value through synergies—but this value is often missed by investors. The complexity of these strategies challenges investor understanding, leading to market undervaluation. We find that improving how firms communicate their technological capabilities—such as using clearer, more familiar language in patent disclosures—can enhance investor recognition and improve market valuations.